2018
DOI: 10.1002/chem.201800489
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐Metal‐Trapping: Concealed Crossover Complexes En Route to Transmetallation?

Abstract: Defined as the transfer of ligands from one metal to another, transmetallation is a common reaction in organometallic chemistry. Its chemical celebrity stems from its role in important catalytic cycles of cross-coupling reactions such as those of Negishi, Sonogashira, Stille, or Suzuki. This article focuses on trans-metal-trapping (TMT), which could be construed as partially complete transmetallations. On mixing two distinct organometallic compounds, of for example lithium with aluminium or gallium, the two me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 64 publications
0
21
0
Order By: Relevance
“…More recently a sophisticated template approach has been reported employing the sodium magnesiate base [Na 4 Mg 2 (TMP) 6 ( n Bu) 2 ]. This powerful method relies on the azametallo ring scaffold, which can override acidity criteria and direct remarkable selective and regiospecific polymetallations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently a sophisticated template approach has been reported employing the sodium magnesiate base [Na 4 Mg 2 (TMP) 6 ( n Bu) 2 ]. This powerful method relies on the azametallo ring scaffold, which can override acidity criteria and direct remarkable selective and regiospecific polymetallations.…”
Section: Introductionmentioning
confidence: 99%
“…However,s ubsequent in situ electrophilicq uenching studies with iodine revealed am ixture of ortho-, meta-and para-iodoanilines. [29] More recently as ophisticated template approach [30] has been reported employing the sodium magnesiate base [Na 4 Mg 2 (TMP) 6 (nBu) 2 ]. This powerful method relies on the azametallo ring scaffold, which can override acidity criteria and direct remarkable selectivea nd regiospecific polymetallations.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data led to an explosion of interest in what have become known as ‘synergic bases’,2 heterobimetallic reagents of the type (R, R′ = organyl; m = 0–3; M = more electronegative metal; = amide; n = 1–3; M′ = less electronegative metal). Over the subsequent two decades these bases have afforded levels of reactivity,3 regioselectivity4 and functional group tolerance5 not previously available using traditional main group organometallic bases, and they continue to evolve new applications 6. Most work in this field has focused on the directed ortho metalation of functional aromatics, in which M = Zn,1 Cr,7 Fe,8 Mg,9 Al,10 and Mn 11.…”
Section: Introductionmentioning
confidence: 99%
“…However, reactions with substrates sensitive to nucleophilic attack such as azines must be performed at very low temperatures to avoid secondary reactions between arylmetals and functions [13,14,15]. The use of in situ metal traps avoids the use of cryogenic conditions to achieve these reactions [16,17]. We have developed mixed lithium-zinc combinations based on TMP (TMP = 2,2,6,6-tetramethylpiperidino) capable of deprotonating sensitive substrates at temperatures close to rt [18,19,20,21].…”
Section: Introductionmentioning
confidence: 99%